(untitled) (Eduscotech, 2023)
This research aims to determine the standardization of sports facilities and infrastructure at SDN 2 Sugihwaras. This study is qualitative research using a survey method. The data sources will be obtained from building managers and players, who will explain the number and condition of physical education facilities and infrastructure. Data collection techniques include interviews, documentation, and observation sheets, with data analysis using qualitative analysis. The research results show that many facilities and infrastructures for the football branch at SDN 2 Sugihwaras are non-standard, while only a few are categorized as standard, such as the width of the goalpost, soccer balls, and drainage on the football field. For badminton facilities and infrastructure, there are 14 non-standard items, while only 12 are categorized as standard. In volleyball, 8 facilities and infrastructures are non-standard, with only 1 categorized as standard. For futsal, there are 3 non-standard facilities and 8 standard ones. However, the overall number of sports facilities and infrastructure at SDN 2 Sugihwaras is considered very minimal.